Tumor thrombus: incidence, imaging, prognosis and treatment - Quencer, Keith Bertram; Friedman, Tamir; Sheth, Rahul; Oklu, Rahmi (Cardiovascular diagnosis and therapy, 2017)
Intravascular tumor extension, also known as tumor thrombus, can occur in many different types of cancer. Those with the highest proclivity include Wilm's tumor, renal cell carcinoma (RCC), adrenal cortical carcinoma (ACC) and hepatocellular carcinoma (HCC). The presence of tumor thrombus markedly worsens prognosis and impacts treatment approach. Imaging plays a key role in its diagnosis. Endovascular methods also play a large role in treatment.